Determination and Application of Pont's Index in Turkish Population - Ahmet Arif Celebi; Enes Tan; Ibrahim Erhan Gelgor (The Scientific World Journal)
Disharmony between tooth size and dental arch size induces orthodontic problems. So, dental indices were identified by various authors. One of these is Pont who determined a method of prediction of the ideal dental arch width which has become known as Pont's Index. The purpose of this study was to assess the applicability of Pont's Index to a Turkish population and to compare the results with those obtained from studies of different ethnic subjects. The sample comprised 64 male subjects and 78 female subjects with age range from 14 to 15 years. Measurements were obtained directly from plaster casts; they included mesiodistal crown diameters of the four maxillary incisors, as well as interpremolar and intermolar maxillary arch widths as specified by Pont. Correlation coefficients determined between the measured arch width values and those calculated according to Pont's Index were low in all cases, with r values ranging from 0.02 to 0.36. It was concluded that Pont's Index should not be used to predetermine ideal arch width values in Turkish individuals.